Nuevos ensayos de filosofía de la biología - Torretti, Roberto (Revista de Filosofía, 2008)
A review essay concerning The Cambridge Companion to the Philosophy of Biology, David L. Hull and Michael Ruse, eds. (Cambridge: Cambridge University Press, 2007; xxviii + 513 pp.) and Philosophy of Biology, Mohan Matthen and Christopher Stephens, eds. (Amsterdam, Elsevier/North-Holland, 2007; xx + 618 pp.)